Peningkatan Motivasi Siswa Sekolah Dasar dalam Pembelajaran IPS Menggunakan Media Audio Visual - Rusmiati, Rusmiati; Puswiartika, Dhevy; Gamar, Mahfud Mahmud (Jurnal Studi Guru dan Pembelajaran, 2024)
This research aims to describe teachers' efforts to increase student motivation, find out the learning media used and the magnitude of the increase in student motivation in learning social studies using audio-visual media. The subjects of this research were fifth grade students at SDN Dampala, Bahodopi District, who were active in the even semester of the 2023/2024 academic year. This research uses a qualitative description method based on an assessment rubric in the form of observation sheets, documentation and interviews. The results of the research show that teachers' efforts to increase student motivation can be seen from the better student response to the learning process, collaboration between students and also between students and teachers, as well as the creation of a supportive learning environment which is an important factor in increasing student motivation. The use of learning media can be seen from. The positive impact on student motivation during the learning process and increasing student motivation in social studies learning shows that effective integration of audio-visual media in learning can increase students' attention to social studies learning material.